Strategies for Teaching Reading through Vocabulary Memorization at Al-Hasaniyah Islamic Junior High School, Gunung Geni, Probolinggo - Dimas Suyitno Putra; Edi Kurniawan Farid; Ainur Rofiq Sofa (Universitas Al-Amien Prenduan, 2026)
This study aims to analyze the implementation of reading instruction strategies through vocabulary memorization in Arabic language learning at Al-Hasaniyah Islamic Junior High School. Reading skill is one of the essential competencies in learning Arabic because it enables students to understand written texts and expand their linguistic knowledge. However, many students face difficulties in comprehending Arabic texts due to limited vocabulary mastery. Therefore, an effective learning strategy is required to improve students’ reading ability.This research uses a qualitative field research approach. Data were collected through classroom observations, interviews with Arabic language teachers, and documentation. The data were then analyzed using descriptive qualitative analysis to identify the strategies used in teaching reading through vocabulary memorization.The results show that the teacher applies several strategies, including introducing new vocabulary before reading activities, guiding students to memorize vocabulary repeatedly, and integrating vocabulary practice with reading exercises. These strategies help students understand the meaning of texts more easily and improve their reading comprehension.The study concludes that vocabulary memorization plays an important role in supporting students’ reading skills in Arabic learning. Effective vocabulary teaching strategies can enhance students’ comprehension and make the reading learning process more meaningful. Keywords: Arabic learning, reading skills, vocabulary memorization, learning strategies